Anatomical Measurement as a Reference for Functional Endoscopic Sinus Surgery Based on CT Scans and Dissections - Zanuncio, Andressa Vinha; Amaral, Flávia Gontijo; Pereira, Marcell de Barros Duarte; Nunes, Flávio Barbosa; Guimarães, Roberto Eustáquio Santos (International Archives of Otorhinolaryngology, 2024)
Introduction Diseases of the paranasal sinuses, nasal cavities, and those related to the skull base can be treated with nasal endoscopic surgery. Anatomical references are essential to safely perform these surgeries.Objective To measure and compare the distance from the posterior wall of the maxillary sinus to the anterior skull base in cadavers and on computed tomography (CT) scans to determine a measurement as an anatomical reference in imaging exams for sinus and anterior skull base surgery.Methods In dissections and CT scans, we took measurements from the most upper and medial point of the posterior wall of the maxillary sinus (point A) to the point where the skull base deflects and the anterior sphenoid wall is formed (Δ 90°; point B), in the right and left nasal cavities. We used 51 cadavers aged ≥ 18 years in the present research.Results The measurements obtained from CT scans and dissections were greater than 1.5 cm in all cadavers, and they were positively correlated. The 1-cm increase in the AB-tomography measurement corresponded to the 1.08-cm increase to the right and 1.07-cm to the left in the AB-dissection measurement.Conclusion The CT measurements may be considered a reliable tool to promote safe and effective access to the paranasal sinuses, matching the distance that should be dissected until the anterior base of the skull.
Keywords: endoscopic surgery; FESS; skull base; paranasal CT scans; paranasal sinuses